Fenomena No Viral No Justice Pada Proses Ganti Kerugian Korban Salah Tangkap (Studi Kasus Pada Perkara Mbah Omen dengan Nomor Perkara (1/Pid.Pra/2019/PN.Kbu) ) - Abdurrachman (Legalita, 2025)
In the development of social media, we know the strength of netizens. Internet users in Indonesia, known as netizens, are very critical in defending truth and justice. After going through a long series of trials and having been proven through the Judicial Process and it was stated that Mbah Omen was only a victim of wrongful arrest and the State was obliged to compensate for the losses, all that remained was the follow-up process, namely the Execution process for compensation, which had been waiting for almost 5 years and there had been no news that the victim had been wrongly arrested by North Lampung Police officers, Oman Abdurrahman alias Mbah Oman through his Legal Counsel, Abdurachman asked the State to take responsibility through the Application Route to Netizens, namely the Viral Phenomenon. In preparing this research, the author applied the Normative Juridical research method with a conceptual approach and a statutory approach. In compensation for losses due to the actions of law enforcement officials, the party who has the right to submit a request for compensation for the actions of the law enforcement officials is the suspect, defendant or convict. Oman Abdurohman can apply for compensation and execution using the viral method which is now trendy with the term No Viral No Justice